Internet use by businesses in Old and New EU member countries - Patrice Muller; Pau Salsas (Transformation, Integration and Globalization Economic Research (TIGER), 2004)
In recent years, the potential use of information and communication technologies (ICT) and, more particularly, the Internet as an instrument of change, and economic development and growth has attracted considerable attention. Whereas much of the policy discussion has focused on the promotion of the use of the Internet by households, business and governments, the empirical evidence of the determinants of the Internet take-up in various countries is still relatively limited. So far, a number of country-specific studies have examined the determinants and benefits of ICT use by businesses, but there is very limited empirical evidence on the reasons for the observed wide cross-country differences in Internet take-up by businesses. In the present study we use data from the recently e-Business Survey 2003 to examine why Internet usage by businesses in the 25 EU Member States differs.
Keywords: 330; Internet; EU-Mitgliedschaft; EU-Staaten